2017
DOI: 10.18203/2320-1770.ijrcog20171504
|View full text |Cite
|
Sign up to set email alerts
|

A study of antenatal anxiety: comparison across trimesters

Abstract: Background: The aim of present study was to investigate the antenatal anxiety across all three trimesters of pregnancy.Methods: This is a cross sectional, observational study for which data is collected from consenting subjects attending antenatal Out Patients department for routine antenatal checkup. Data included socio demographic information’s and Hospital Anxiety and Depression Scale and statistical analysis done.Results: Out of 169 Pregnant females 27.8% were during first trimester, 40.8% during second tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Among Indian studies, Madhavaprabhakaran et al25 with the help of the Pregnancy Specific Anxiety Scale (PSAS), found that all women during the first trimester had some degree of pregnancy specific anxiety, which was mostly the moderate form in 89.4% of the women. A lower prevalence rate of 28.4% throughout all the trimesters was seen among pregnant women in Bhubaneswar for which the Hospital Depression and Anxiety Scale was used for measurement 26. This disparity in the prevalence rates could be attributed to differences in the psychometric properties of measuring scales that were used; and also to the sociodemographic and sociocultural heterogeneity and diversity of the study population.…”
Section: Discussionmentioning
confidence: 90%
“…Among Indian studies, Madhavaprabhakaran et al25 with the help of the Pregnancy Specific Anxiety Scale (PSAS), found that all women during the first trimester had some degree of pregnancy specific anxiety, which was mostly the moderate form in 89.4% of the women. A lower prevalence rate of 28.4% throughout all the trimesters was seen among pregnant women in Bhubaneswar for which the Hospital Depression and Anxiety Scale was used for measurement 26. This disparity in the prevalence rates could be attributed to differences in the psychometric properties of measuring scales that were used; and also to the sociodemographic and sociocultural heterogeneity and diversity of the study population.…”
Section: Discussionmentioning
confidence: 90%
“…This is similar to study done in Bhubaneshwar that reported significantly higher anxiety scores for third trimester (p =0.000). 12 Another study done by Madhavanprabhakaran et al in Kerala suggested a significantly high prevalence of pregnancy-specific anxiety during the third trimester. 20 However, another study done in Bangalore reported increased anxiety in early pregnancy with significantly higher levels of anxiety during the first trimester (47.8%).…”
Section: Discussionmentioning
confidence: 96%
“…This is in collaboration to a study done in Bhubaneshwar by Priyambada K in which most of the participants belonged to second trimester (40.8%), followed by third trimester (31.4%) and 27.8 % belonging to first trimester. 12 The socio demographic components of the antenatal women were compared with antenatal anxiety. The age group of 18-25 years (p = 0.03) and literacy status of secondary education (p = 0.008) reported to be risk factors for prenatal anxiety according to our study signifying that becoming pregnant at a young age itself might be a cause of increased anxiety among women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kecemasan di kehamilan trimester ketiga terdapat banyak tantangan fisik dan emosional, ibu akan merasakan ketidaknyamanan fisik kembali yang semakin kuat menjelang persalinan. Selain itu, perasaan cemas mengingat bayi dapat lahir kapan pun, memikirkan apakah nanti bayinya akan terlahir normal dan terkait persalinan apakah ia mampu melahirkan bayinya [1].…”
Section: Pendahuluanunclassified